User experience design (UXD) of mobile application: an implementation of a case study - Yazid, Mariam Azwa; Jantan, Azrul Hazri (Faculty of Electronic and Computer Engineering, Universiti Teknikal Malaysia Melaka, 2017)
The success of an application is tied directly to the degree of the user acceptance. Analyzing user expectation and acceptance prior to the development process is vital to make a successful product. User experience design (UXD) is the research field which identified users’ needs, expectation and acceptance when there is an interaction with a product or service. Due to the lack of UXD guidelines, we will be presenting the UXD strategy for mobile flight booking ticket application (MFBTA). MFBTA is a complex application that has various type of transaction inclusive the dynamic interaction and ecommerce component that requires perceivable UXD elements. Based on the observation, it shows that UXD in MFBTA is yet to be improved in order to achieve a high degree of user acceptance and expectation.